2017
DOI: 10.19173/irrodl.v18i2.3033
|View full text |Cite
|
Sign up to set email alerts
|

Why Study on a MOOC? The Motives of Students and Professionals

Abstract: Massive Open Online Courses have emerged as a popular mechanism for independent learners to acquire new knowledge and skills; however, the challenge of learning online without dedicated tutor support requires learners to self-motivate. This study explores the primary motivations reported by participants in two MOOCs: Fundamentals of Clinical Trials and Introduction to Data Science (n=970). Each MOOC drew a diverse cohort of participants ranging from professionals working in the field to students preparing to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 20 publications
6
65
1
2
Order By: Relevance
“…A MOOC is recognized as a collaborative learning environment, which requires students to possess socio-communication competencies to guarantee active participation. According to Milligan and Littlejohn (2017), one of the main motivations of MOOC students is forming social relationships with other learners. Therefore, Willis (2013) points out that improved socio-communication skills are fundamental for the success of collaborative learning in MOOC environments, in which the presence of learners' communities is recognized as an essential factor.…”
Section: Discussionmentioning
confidence: 99%
“…A MOOC is recognized as a collaborative learning environment, which requires students to possess socio-communication competencies to guarantee active participation. According to Milligan and Littlejohn (2017), one of the main motivations of MOOC students is forming social relationships with other learners. Therefore, Willis (2013) points out that improved socio-communication skills are fundamental for the success of collaborative learning in MOOC environments, in which the presence of learners' communities is recognized as an essential factor.…”
Section: Discussionmentioning
confidence: 99%
“…In past few years, a significant body of literature on motivation in MOOCs has been published [36,37]. There have been studies that approach the motivation of the learners from various angles.…”
Section: Theoretical Framework and Research Backgroundmentioning
confidence: 99%
“…With regard to the learning process, two subcategories of research objects were identified: the determinants of learning, and interactions in the MOOCs. For instance, the research questions addressing the determinants of learning included how participants self-regulated their learning Kizilcec et al, 2017;Littlejohn et al, 2016;, people's motivations for participating or learning in a MOOC (Milligan & Littlejohn, 2017;Rieber, 2017;Shapiro et al, 2017;Stich & Reeves, 2017), and the learner behaviour in the course (de Lima & Zorrilla, 2017;Kahan, Soffer & Nachmias, 2017). Articles focusing on interactions in MOOCs examined the modes of discussion that characterised the participation of learners in forums (Gillani & Eynon, 2014;Zhang et al, 2016), the modes of communication offered to learners, namely asynchronous or synchronous (Li et al, 2014), the processes of interaction between users and organisers in the case of cMOOCs (Andersen & Ponti, 2014), or the modes of interaction and their role in the co-construction of new knowledge (Kellogg et al, 2014).…”
Section: Categories Of Research Objectsmentioning
confidence: 99%